Pengaruh Tingkat Kematangan dan Suhu Penyimpanan Terhadap Mutu Buah Terong Belanda (Cyphomandra betacea) - Elisa Julianti (Jurnal Hortikultura Indonesia, 2011)
Tamarillo is a perishable fruit. To ensure the highest fruit quality tamarillos must be harvested at an appropriate stage of maturity. In the present study, effects of maturity stage and storage temperature on the physical and chemical characteristics of tamarillo were determined. The fruits were harvested at three stages i.e. immature, mature, and ripe and kept in cold storage at 10 oC and at ambient conditions (28±2 oC) for a period of 15 days. The fruits were evaluated for quality variables at harvest and after 5, 10 and 15 days of storage. During investigation period fruit quality variables changed according to stage of harvest. An increase in weight loss, total soluble solid (TSS) was observed with the advancement of maturity stages and storage period. In contrast, vitamin C content and titratable acidity followed a linear decline with storage and advancement of maturity stages. Fruits harvested at optimum stage retained maximum TSS, titratable acidity and sensory quality (color, flavor and texture) score during storage of 10 days at ambient and 15 days at cold temperature.Key words : Tamarillo, maturity stage, storage, fruit quality